2020
DOI: 10.1186/s12889-020-09382-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health professionals’ perception of health literacy in Rhode Island community health centers: a qualitative study

Abstract: Background: Limited health literacy is linked with poor health behaviors, limited health care access, and poor health outcomes. Improving individual and population health outcomes requires understanding and addressing barriers to promoting health literacy. Methods: Using the socio-ecological model as a guiding framework, this qualitative study (Phase 1 of a larger ongoing project) explored the interpersonal and organizational levels that may impact the health literacy levels of patients seeking care at federal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…In addition, the welfare state encourages the development of informal care- which is a type of care that provided by family members to meet older people's unmet care needs- such as the provision of a supporting care allowance for family caregivers ( 2 – 4 ). However, older people in China still have high levels of unmet care needs ( 4 ) owing to the lack of informal care resources and insufficient formal care from both institutional and residential care ( 5 ). Furthermore, the relatively low level of assistance provided by China's care policy makes care services too expensive for older people to cover by themselves, despite the proportion paid by the state ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the welfare state encourages the development of informal care- which is a type of care that provided by family members to meet older people's unmet care needs- such as the provision of a supporting care allowance for family caregivers ( 2 – 4 ). However, older people in China still have high levels of unmet care needs ( 4 ) owing to the lack of informal care resources and insufficient formal care from both institutional and residential care ( 5 ). Furthermore, the relatively low level of assistance provided by China's care policy makes care services too expensive for older people to cover by themselves, despite the proportion paid by the state ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The care managers' aim in going through selfassessment scales together with the patient was to give the person the opportunity to ask questions based on individual needs. Previous studies have shown that the content of the material is thereby integrated on a deeper level, and through the interaction it becomes easier for patients to then apply the information on their own [6,7,31,32]. Previous studies also show that using different strategies in combination with different methods improves the patient's understanding, compliance and health outcomes and strengthens the patient's health literacy [6,7,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The individual ability to influence one's health varies throughout life. Therefore, it is important to reconsider individuals' health knowledge at meetings in health care [4,6,8,15,[21][22][23] and to adapt communication, support and strategies based on the individual's needs [7,18,20,23,24]. Patients with mental illness often have low confidence in their own abilities and may have difficulty expressing their needs, which often makes the healthcare encounter more challenging [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If healthcare professionals themselves have health literacy needs, then this can hinder their abilities to support their patients. In an era that has a strong focus on patient-centred care, it becomes critical that healthcare professionals understand and can detect, accommodate and respond appropriately to the health literacy diversity of their communities [ 18 , 19 , 20 ]. The measurement of the health literacy strengths, needs and preferences of students studying the health professions enables early support for students’ own health literacy and helps to identify and address gaps in the curriculum for their health literacy training for their future roles as healthcare professionals [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%